COVID-19 in Children with Chronic Kidney Disease; Does it Differ Much? - Baltu, Demet; Kurt-Sukur, Eda Didem; Tastemel Ozturk, Tugba; Gulhan, Bora; Ozaltin, Fatih; Duzova, Ali; Topaloglu, Rezan (Klinische Pädiatrie, 2024)
Background COVID-19 is known to have a mild course in children, however more data on pediatric chronic kidney disease (CKD) is needed. We aimed to assess the incidence and severity of COVID-19 in pediatric CKD patients.Methods A questionnaire including demographics, COVID-19 history, symptoms, and vaccination status was applied to patients with CKD. We also retrospectively reviewed the presentation and outcomes of SARS-CoV-2 infection in this patient group from March 2020 to December 2021.Results 220 patients were included, 48 were found to have experienced COVID-19. There was no significant difference regarding age, gender, underlying kidney disease, CKD stage, dialysis status, type or number of immunosuppressive medications, and glomerular filtration rate between patients with and without COVID-19. Most were infected by a household member (43.8%) and during outpatient or inpatient care (18.8%). Four (8.3%) were asymptomatic, and 43 (89.6%) had mild infection. Severe COVID-19 was observed in only one patient. Eleven (22.9%) patients with COVID-19 were previously vaccinated. Acute kidney injury was detected in 4 (8.3%); as stage 1 in all. Median follow-up after COVID-19 was 4.6 months. All patients fully recovered, and no renal disease flare or death was observed.Conclusions Although the vaccination rate was low in our cohort, the majority of the children with COVID-19 showed a mild course. Along with the vaccination, general precautions seemed to be successful for this population.
Keywords: COVID-19; CKD; nephrotic syndrome; renal transplantation; immunosupression